Usefulness of collision warning inter-vehicular system. (22nd September 2010) - Lambert, Alain; Gruyer, Dominique; Busson, Anthony; Mansoor Ali, Husnain
This paper studies the contribution and the impact of Inter-Vehicular Communications (IVC) in a vehicles string. We suppose that all, or, a subset of the vehicles are equipped with radio communication devices, enabling communication between them. We evaluate the benefit of the dissemination of warning messages for the reduction of accidents. More precisely, we evaluate and compare the number of vehicles involved in a multi-vehicles crash caused by an accident, with and without the use of IVC. We show that even when a low proportion of vehicles uses IVC, the number of collisions is drastically reduced.